Fabrication of GaOx based crossbar array memristive devices and their resistive switching properties. (12th May 2020) - Joko, Mamoru; Hayashi, Yusuke; Tohei, Tetsuya; Sakai, Akira
Abstract: Memristive devices attract much attention for the application to neuromorphic computing. Here we focus on amorphous GaO x based memristive devices and their integration as a crossbar architecture which is mandatory to improve parallelism in computing and essential to future power-saving, high-speed and reliable artificial neural networks (ANN). Fabricated Pt/GaO x /ITO crossbar array memristive devices with 3 × 3 μ m 2 crosspoints exhibit non-filamentary reversible bipolar resistive switching (RS) without any electroforming processes. We demonstrate the gradual resistance change by repeating voltage sweep and applying pulse voltages. The expression of spike-timing-dependent plasticity property, one of synaptic functions in neuromorphic devices, is also successful in the present device. The obtained results strongly suggest that the drift of oxygen vacancies in GaO x plays an important role in the RS behavior and the GaO x based crossbar array memristive devices have a great potential for hardware implementation of ANN.